Dinosaur dreams - Ahlberg, Allan; Amstutz, Andre (London : Little Mammoth, 1991)
Three skeletons enter each other's dreams about dinosaurs.
Keywords: Dinosaurs -- Fiction; Dreams -- Fiction; Skeleton -- Fiction